Conscientious objection in Italy. Issue 2 (26th May 2014) - Minerva, Francesca
Abstract : The law regulating abortion in Italy gives healthcare practitioners the option to make a conscientious objection to activities that are specific and necessary to an abortive intervention. Conscientious objectors among Italian gynaecologists amount to about 70%. This means that only a few doctors are available to perform abortions, and therefore access to abortion is subject to constraints. In 2012 the International Planned Parenthood Federation European Network (IPPF EN) lodged a complaint against Italy to the European Committee of Social Rights, claiming that the inadequate protection of the right to access abortion implies a violation of the right to health. In this paper I will discuss the Italian situation with respect to conscientious objection to abortion and I will suggest possible solutions to the problem.